Examining Developmental Dialogue: the Emergence of Transformative Agency - Heikkila, Heli; Seppänen, Laura (Outlines. Critical Practice Studies, 2014)
The intervention method of Developmental Dialogue, originally developed by Laura Mott (1992), has been further elaborated to promote employees’ professional development and well-being. The aim of formative interventions is to enhance the agency of participants. There is particular interest in transformative agency, which is defined as participants’ capacity to take purposeful actions to change their work activity. By applying six types of agency expressions, this paper examines how transformative agency emerges in an interaction between a DD participant and the interventionist. The agency expressions are analysed in the context of explicit and implicit intervention tools and objects of talk. The analysis yields a new category called reframing agency which is of interest particularly from a work-related well-being perspective. We interpret the findings with the notion of a contradictory object within the cycle model of professional development. The case suggests that changes in work, as interpreted by the researchers do not always fully grasp the participant’s sense of collective work. Finally, at the end of the paper we propose ideas for further research.